Upaya pembaharuan dalam pendidikan dan pengajaran Cece Wijaya, Djaja Djadjuri, A. Tabrani Rusyan ; editor, Tjun Surjaman, Wilson Nadeak - WIJAYA, Cece; Rusyan, A. Tabrani; Jajuri, Jaja (1992)
XI, 192 hlm ilus 21 cm